2018
DOI: 10.2298/abs180812043h
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Arg753Gln Toll-like receptor 2 and Asp299Gly Toll-like receptor 4 genetic variations and susceptibility to colorectal cancer in Southern Iran

Abstract: Relationship between Arg753Gln Toll-like receptor 2 and Asp299Gly Toll-like receptor 4 genetic variations and susceptibility to colorectal cancer in Southern Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…1). [12–15,17–76] Among them, there were 25,969 people in the case group and 32,119 in the control group. The diseases involved in case groups include prostate cancer, lung cancer, gastric cancer, hepatocellular carcinoma, colorectal cancer, etc.…”
Section: Resultsmentioning
confidence: 99%
“…1). [12–15,17–76] Among them, there were 25,969 people in the case group and 32,119 in the control group. The diseases involved in case groups include prostate cancer, lung cancer, gastric cancer, hepatocellular carcinoma, colorectal cancer, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Of all the TLRs that are functional in humans, the single nucleotide polymorphisms (SNPs) of five TLR genes— TLR2 , 3 , 4 , 5 , and 9 —have been reported to be involved in modulating the risk of CRC extensively [ 17 , 21 , 22 , 25 , 28 , 49 , 101 , 102 ]. SNPs in any gene results in the change of amino acid sequence (missense/frameshift) which alters the structure and activity of the involved protein [ 103 ].…”
Section: Toll-like Receptor Polymorphism and Colorectal Cancermentioning
confidence: 99%
“…9 No. 3 A study in the south of Iran on 150 patients with colorectal cancer and 150 control people showed a significant relationship between the TLR2 Arg753Gln polymorphism and colorectal cancer [32]. A metaanalysis study revealed that rs5743708 polymorphism was related to hepatocellular carcinoma (HCC) and decreased survival of patients with stages III and IV of advanced colon cancer [33].…”
Section: Vol 9 Nomentioning
confidence: 99%